2017
DOI: 10.5194/acp-2017-245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connecting smoke plumes to sources using Hazard Mapping System (HMS) smoke and fire location data over North America

Abstract: Abstract. Fires represent an air quality challenge because they are large, dynamic and transient sources of particulate matter and ozone precursors. Transported smoke can deteriorate air quality over large regions. Fire severity and frequency are likely to increase in the future, exacerbating an existing problem. Using the National Environmental Satellite, Data and Information Service (NESDIS) Hazard Mapping System (HMS) smoke data for North America for the period 2007 to 2014, we examine 10 a subset of fires … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 26 publications
8
58
0
Order By: Relevance
“…As well, in the springtime, smoke plumes from Central America can be transported to the SE region, as reported in the studies of Park et al (2003) and Wang et al ( , 2009. Brey, Ruminski, et al (2018) combined the HMS product and HYSPLIT forward trajectory data to connect summertime (June-September) smoke plumes to their sources (see their Figure 13). They found that in the NW, SW, and SE, smoke hours were contributed mainly by fires within these regions, although smoke was exchanged to a significant extent among western regions.…”
Section: 1029/2019jd031372mentioning
confidence: 87%
See 3 more Smart Citations
“…As well, in the springtime, smoke plumes from Central America can be transported to the SE region, as reported in the studies of Park et al (2003) and Wang et al ( , 2009. Brey, Ruminski, et al (2018) combined the HMS product and HYSPLIT forward trajectory data to connect summertime (June-September) smoke plumes to their sources (see their Figure 13). They found that in the NW, SW, and SE, smoke hours were contributed mainly by fires within these regions, although smoke was exchanged to a significant extent among western regions.…”
Section: 1029/2019jd031372mentioning
confidence: 87%
“…(2019) and Brey, Ruminski, et al (2018), we flag data as "smoky" when the AERONET sites are overlapped by an HMS smoke polygon. There are several limitations to using the HMS product to determine when smoke may be present in surface observations, as noted in O' Dell et al (2019).…”
Section: The Hazard Mapping System Fire and Smoke Product (Hms)mentioning
confidence: 99%
See 2 more Smart Citations
“…The HMS smoke product is produced using multiple NASA and NOAA satellite products (Rolph et al, 2009). Smoke in the atmospheric column is detected using both visible and infrared imagery and is fully described in Brey et al (2017). The extent of smoke plumes within the HMS dataset represents a conservative estimate, and no information is provided on the vertical extent or vertical placement of the plumes.…”
Section: Smoke Eventsmentioning
confidence: 99%